Sensitive quantification of fibroblast activation protein and high-throughput screening for inhibition by FDA-approved compounds - Čermáková, Kateřina; Šimková, Adéla; Wichterle, Filip; Kryštůfek, Robin; Staňurová, Jana; Vaníčková, Zdislava; Bušek, Petr; Konvalinka, Jan; Šácha, Pavel (European journal of medicinal chemistry, 2024)
Fibroblast activation protein (FAP) has been extensively studied as a cancer biomarker for decades. Recently, small-molecule FAP inhibitors have been widely adopted as a targeting moiety of experimental theranostic radiotracers. Here we present a fast qPCR-based analytical method allowing FAP inhibition screening in a high-throughput regime. To identify clinically relevant compounds that might interfere with FAP-targeted approaches, we focused on a library of FDA-approved drugs. Using the DNA-linked Inhibitor Antibody Assay (DIANA), we tested a library of 2667 compounds within just a few hours and identified numerous FDA-approved drugs as novel FAP inhibitors. Among these, prodrugs of cephalosporin antibiotics and reverse transcriptase inhibitors, along with one elastase inhibitor, were the most potent FAP inhibitors in our dataset. In addition, by employing FAP DIANA in the quantification mode, we were able to determine FAP concentrations in human plasma samples. Together, our work expands the repertoire of FAP inhibitors, analyzes the potential interference of co-administered drugs with FAP-targeting strategies, and presents a sensitive and low-consumption ELISA alternative for FAP quantification with a detection limit of 50 pg/ml.
Keywords: DIANA; Fibroblast activation protein; Endopeptidases; Gelatinases; Structure-Activity Relationship; knihovny malých molekul; High-throughput screening; molekulární struktura; membránové proteiny; Molecular Structure; Membrane Proteins; vztah mezi dávkou a účinkem léčiva; FAP quantification; vztahy mezi strukturou a aktivitou; rychlé screeningové testy; schvalování léčiv; lidé; United States; Humans; High-Throughput Screening Assays; serinové endopeptidasy; endopeptidasy; cefalosporiny; Spojené státy americké; Drug Approval; Dose-Response Relationship, Drug; Small Molecule Libraries; Úřad Spojených států pro potraviny a léky; Serine Endopeptidases; United States Food and Drug Administration; Cephalosporins; želatinasy